Limiting amino acids for Holstein steers fed soybean hull-based diets - R.H. Greenwood; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2000)
A study was conducted to determine the limiting amino acids for cattle fed soybean hullbased diets. Ruminally cannulated Holstein steers (335 lb) were maintained in metabolism crates, fed the same basal diet (73% soyhulls, 19% alfalfa), and given the same intraruminal infusions (400 g/day acetate to increase energy supply without increasing microbial protein supply). Steers were infused into the abomasum with a complete mixture of the 10 essential amino acids or the mixture with histidine; tryptophan; arginine; phenylalanine; or the three branched-chain amino acids (leucine, isoleucine, and valine) removed. Nitrogen retention was reduced by removal of either histidine or the branched-chain amino acids, suggesting that those amino acids were limiting.
Keywords: Cattlemen' s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Steers; Soybean hulls; Amino acids